Evaluation of Bio M pylori serologic test and C-13 urea breath test for H. pylori infection in children with recurrent abdominal pain: a pilot study - Mira Dewita; Badriul Hegar Syarif; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2010)
Background Diagnosing Helicobacter pylori infection in childrenis still a problem. Urea breath test is the gold standard for noninvasivediagnostic test, but it is expensive and not available inmost hospitals. The Bio M Pylori serologic test has good diagnosticvalue in adults, less expensive and more practical, but had neverbeen evaluated in children.Objective To determine the prevalence of H. pylori infection andthe diagnostic accuracy of Bio M Pylori serologic test in childrenwith recurrent abdominal pain.Methods This study was conducted in May - June 2009. Childrenaged 12-15 years with recurrent abdominal pain were examinedwith urea breath test and the Bio M Pylori serologic test.Sensitivity, specificity, area under the curve (AUC), predictivevalues, and likelihood ratios were calculated for the Bio M Pyloriserologic test.Results Most subjects aged 13 years (83%). Girls outnumberedboys, and most were undernourished. The prevalence ofH. pyloriinfection detected by urea breath test and Bio M Pylori serologictest was 8% and 52%, respectively. The Bio M Pylori serologictest had sensitivity and specificity of 100% and 53%, respectively.Area under the curve (AUC) was 0.764. Positive and negativepredictive values were 16 and 100%, whereas positive andnegative likelihood ratios are 2.12 and 0. The overall accuracyof this test is 5 7%Conclusions The Bio M Pylori serologic test has high sensitivityvalue (100%). This diagnostic kit can be considered as a goodpre-endoscopic screening tool in children with recurrentabdominal pain caused by H. pylori infection.